Particle size distribution in soils and marine sediments by laser diffraction using Malvern Mastersizer 2000—method uncertainty including the effect of hydrogen peroxide pretreatment - Ingeborg Callesen; Hannes Keck; Thorbjørn Joest Andersen (Journal of Soils and Sediments, 2018)

The natural abundance of 15N in litter and soil profiles under six temperate tree species: N cycling depends on tree species traits and site fertility - Ingeborg Callesen; Lars Ola Nilsson; Inger Kappel Schmidt; Lars Vesterdal; Per Ambus; Jesper Riis Christiansen; Peter Högberg; Per Gundersen (Plant and Soil, 2013)

Role of six European tree species and land‐use legacy for nitrogen and water budgets in forests - JESPER RIIS CHRISTIANSEN; LARS VESTERDAL; INGEBORG CALLESEN; BO ELBERLING; INGER KAPPEL SCHMIDT; PER GUNDERSEN (Global Change Biology, 2010)
Water and nutrient fluxes for single stands of different tree species have been reported in numerous studies, but comparative studies of nutrient and hydrological budgets of common European deciduous tree species are rare. Annual fluxes of water and inorganic nitrogen (N) were established in a 30‐year‐old common garden design with stands of common ash ( Fraxinus excelsior ), European beech ( Fagus sylvatica L.), pedunculate oak ( Quercus robur ), small‐leaved lime ( Tilia cordata Mill.), sycamore maple ( Acer pseudoplatanus ) and Norway spruce ( Picea abies [L.] Karst .) replicated at two sites in Denmark, Mattrup and Vallø during 2 years. Mean annual percolation below the root zone (mm yr −1 ±SE, n =4) ranked in the following order: maple (351±38)>lime (284±32), oak (271±25), beech (257±30), ash (307±69)≫ spruce (75±24). There were few significant tree species effects on N fluxes. However, the annual mean N throughfall flux (kg N ha −1 yr −1 ±SE, n =4) for spruce (28±2) was significantly larger than for maple (12±1), beech (11±1) and oak (9±1) stands but not different from that of lime (15±3). Ash had a low mean annual inorganic N throughfall deposition of 9.1 kg ha −1 , but was only present at Mattrup. Annual mean of inorganic N leaching (kg ha −1 yr −1 ±SE, n =4) did not differ significantly between species despite of contrasting tree species mean values; beech (25±9)>oak (16±10), spruce (15±8), lime (14±8)≫ maple (1.9±1), ash (2.0±1). The two sites had similar throughfall N fluxes, whereas the annual leaching of N was significantly higher at Mattrup than at Vallø. Accordingly, the sites differed in soil properties in relation to rates and dynamics of N cycling. We conclude that tree species affect the N cycle differently but the legacy of land use exerted a dominant control on the N cycle within the short‐term perspective (30 years) of these stands.

Throughfall Nitrogen Deposition Has Different Impacts on Soil Solution Nitrate Concentration in European Coniferous and Deciduous Forests - Hanne L. Kristensen; Per Gundersen; Ingeborg Callesen; Gert Jan Reinds (Ecosystems, 2004)